2019
DOI: 10.3390/jcm8122038
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease in Rheumatoid Arthritis Remains a Challenge for Clinicians

Abstract: Interstitial lung disease (ILD) is a serious complication of rheumatoid arthritis (RA) contributing to significantly increased morbidity and mortality. Other respiratory complications, such as chronic obstructive pulmonary disease and bronchiectasis, are frequent in RA. Infections and drug toxicity are important differential diagnoses and should be considered in the diagnostic work-up of patients with RA presenting with respiratory symptoms. This review provides an overview of the epidemiology and pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 106 publications
1
48
0
4
Order By: Relevance
“…Interstitial lung disease (ILD) is one of the most feared complications in patients with rheumatoid arthritis (RA), increasing their morbidity and mortality [ 1 , 2 ]. Although ILD frequently develops in patients with established RA, it may also be presented as the initial or single manifestation of an unidentified RA [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interstitial lung disease (ILD) is one of the most feared complications in patients with rheumatoid arthritis (RA), increasing their morbidity and mortality [ 1 , 2 ]. Although ILD frequently develops in patients with established RA, it may also be presented as the initial or single manifestation of an unidentified RA [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial lung disease (ILD) is one of the most feared complications in patients with rheumatoid arthritis (RA), increasing their morbidity and mortality [ 1 , 2 ]. Although ILD frequently develops in patients with established RA, it may also be presented as the initial or single manifestation of an unidentified RA [ 1 , 2 , 3 ]. In this regard, the identification of an underlying RA in ILD patients remains a challenge, considering that RA-ILD + shares clinical, pathological, and epidemiological similarities with idiopathic pulmonary fibrosis (IPF), the most common and severe ILD [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking was reported by about 61% of patients with RA. Several studies have shown that smoking is a risk factor for the occurrence and the progression of RA [ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few hazard factors for improvement of ILD in patients with RA have been recognized [ 23 ]. The most reliably revealed hazard factors incorporate more established age and male gender [ 24 ], cigarette smoking [ 25 ], positive anti- cyclic citrullinated peptide antibodies (against CCP) or IgM rheumatoid factor [ 26 ], and, in certain investigations, RA disease progression [ 22 ]. Smoking is the main preventable hazard factor [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…ILD is a frequent extra-articular involvement, which can deteriorate rather rapidly [18], and imposes a severe burden on affected patients. The therapeutic armamentarium for treating this condition is fortunately becoming richer, although to date there are no specific recommendations on how to treat RA-ILD [19]. Different are the attempts to diagnose RA-ILD without the use of methods that use ionizing radiation, including the use of algorithms that elaborate velcro sounds at chest auscultation [20].…”
Section: Discussionmentioning
confidence: 99%